(untitled) (Cadernos de Sociomuseologia, 2017)
This study addresses some of the ideas developed in the Master’s dissertation entitled "Museum of the High Sertão of Bahia: dialogues between museum of territory and digital cultures" in which it is argued that Museology entails a multidisciplinary approach on memory and heritage. Therefore, the museum, which is also and especially the object of study of Museology, for all that it is, must attend to the growing discourse of digital cultures. In this scenario, the Internet, a fruitful mode of communication, has reshaped the structural bases of the so-called digital culture expressed in a large network of connections in "nodes" that intertwine in what can be called cyberspace. And due to social and technological changes, it is proposed the dialogue between new ICTs and museums, highlighting the similarities and intercessions that may contribute or reflect positively to possible changes in society. It is known that common sense that limits or falsely and mistakenly associates the virtual way of doing something eminently linked to the Internet or lack of materiality. However, the term "virtual" as "power" has almost nothing to do with the common sense. Keywords: museology, virtual, digital, common sense.